2009
DOI: 10.1590/s1808-86942009000600012
|View full text |Cite
|
Sign up to set email alerts
|

Avaliação do ruído em Unidades de Terapia Intensiva

Abstract: Int ensive Care Units are environments with numerous noise sources. In different hospital environments it is recommended to have a sound pressure level between 35 and 45db(A). Aim: To measure the sound pressure levels in three ICU at a hospital in Jundiaí, State of São Paulo, Brazil. Study Design: Observational. Materials and Methods: we used a Minipa model MSL1532C (USA) sound meter, according to the Brazilian Technical Standards (NBR 10151), in order to measure sound levels in the ICUs at different moments, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0
10

Year Published

2010
2010
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 5 publications
1
15
0
10
Order By: Relevance
“…18 Também foram encontrados valores de ruído médio de 65,36dB, em uma UTI geral 19 e de 68dB e 70dB em salas de Unidades de Terapia Intensiva Neonatal, 2 ambos de hospitais universitários da cidade de São Paulo-SP. Da mesma forma a literatura internacional tem apresentado diversos estudos recentes sobre medição do ruído ambiental hospitalar, o que reforça a preocupação com essa temática.…”
Section: Discussionunclassified
“…18 Também foram encontrados valores de ruído médio de 65,36dB, em uma UTI geral 19 e de 68dB e 70dB em salas de Unidades de Terapia Intensiva Neonatal, 2 ambos de hospitais universitários da cidade de São Paulo-SP. Da mesma forma a literatura internacional tem apresentado diversos estudos recentes sobre medição do ruído ambiental hospitalar, o que reforça a preocupação com essa temática.…”
Section: Discussionunclassified
“…Noise exposures may bring about serious functional disorders to the organism. There are literature reports on the relation between high sound pressure levels to other symptoms unrelated to hearing, such as stress, psychological and sleep disorders, memory loss, digestive and circulatory disorders and psychological effects such as irritability, nervousness, tension, among others 3,25,26 . Tinnitus was reported by 29.47%.…”
Section: Documental Analysis Revealed That Environmental Risk Preventmentioning
confidence: 99%
“…Numberless studies have indicated the extreme noise in several hospital environments, and pointed out the need for prevention, as well as, for proper guidance for the professionals, particularly regarding those involved with the area of health, where, theoretically, the awareness for silence should be of major importance [2][3][4][5][6][7] .…”
Section: Source Of Support: Fundação De Amparo à Pesquisa Do Estado Dmentioning
confidence: 99%